Primary design air compressor for force induction engine to be replace turbocharger or supercharger system / Ahmad Fathan M Saleh @ Mohd Nawi - M Saleh @ Mohd Nawi, Ahmad Fathan (2006)
Forced induction system has been widely used in automotive application through an internal combustion engine .In this design of an air compressor which include storage tank that will helps efficiently on compressed air supplied by air compressors. The air compressors which supply the compressed air to the engine can provide the combustion efficient and increase the horsepower. These air compressors may be electrically and/or mechanically driven. An air storage tank working principle is to store the compressed air and provide a rapid compressed air to the combustion chamber.